Polygonum cuspidatum inhibits the growth of osteosarcoma cells via impeding Akt/ERK/EGFR signaling pathways. Issue 2 (1st February 2022) - Zhao, Jun; Pan, Boyu; Zhou, Xinglu; Wu, Chunnuan; Hao, Fengcheng; Zhang, Jie; Liu, Liren
ABSTRACT: Osteosarcoma (OS), the most prevalent bone malignancy, mainly affects children and adolescents. Despite recent advances in multimodal therapy, the overall survival rate for OS patients remains poor. Chinese herb medicine (CHM) is an alternative therapeutic option for multifaceted diseases such as malignant tumors. For centuries in China, polygonum cuspidatum, a classic CHM, has been used to treat several diseases, nevertheless, the mechanisms underlying its therapeutic effects have not been fully elucidated. Through network pharmacology and bioinformatic tools, we evaluated the pharmacological activity of polygonum cuspidatum . We found that it has a potential therapeutic effect on malignant tumors, which was subsequently verified by intragastric administration of polygonum cuspidatum to OS cell xenografted mice models. Next, to establish the action mechanism of polygonum cuspidatum, we built a disease/drug-target PPI network that was made up of 250 core treatment targets against OS using Cytoscape software. Enrichment evaluation for the above targets indicated that polygonum cuspidatum may exert its effects on the cell cycle and apoptosis of OS cells through inhibiting Akt/ERK/EGFR pathways. Finally, the above in silico results were experimentally validated via a series of molecular biological and cell functional analyses. Taken together, the findings show that polygonum cuspidatum has a significant potential for OS treatment, which provides a novel insight into the discovery of CHM-based drug against malignancies. Abbreviations: CC: Closeness centrality; OS: Osteosarcoma; TCM: Traditional Chinese medicine; NSCLC: Non-small cell lung cancer; DC: Degree centrality; CHM: Chinese herb medicine; BC: Betweenness centrality